Seismic behaviour of reinforced concrete columns with lightly transverse reinforcement - Zheng, Fang. (2009)
Through surveys of past studies conducted on the collapse of concrete structures during seismic activities, the lost of column axial strength contributes to the primary cause of failure. Thus, a detail study of column behavior in terms of strength degradation under seismic conditions is critical in determining the trigger mechanism behind structural failures. It’s often known that the initial damage on reinforced concrete columns is associated with flexure and shear which is generated from lateral loadings on the columns. However, it’s the continuous propagation of flexural and shear-stress within the column that brings about degradation of axial strength of the columns that results in the axial-load failure.